Estradiol, obesity and hypogonadism - Stárka, L; Hill, M; Pospíšilová, H; Dušková, M (Physiological research, 2020)
Obesity increases the incidence of hypogonadism in men, and hypogonadism in turn plays a role in obesity. One of the first mechanisms proposed to explain this was a hypothesis based on the principle that obese men have higher estrogen levels, and that increased estrogens provide feedback to the hypothalamic-pituitary-testicular axis, reducing the secretion of gonadotropins and leading to a decrease of overall testosterone levels. This concept has since been questioned, though never completely disproven. In this study we compared hormone levels in three groups of men with differing BMI levels (between 18-25, 25-29, and 30-39), and found correlations between lowering overall testosterone, SHBG and increased BMI. At the same time, there were no significant changes to levels of free androgens, estradiol or the gonadotropins LH and FSH. These findings are in line with the idea that estrogen production in overweight and obese men with BMI up to 39 kg/m(2) does not significantly influence endocrine testicular function.
Keywords: senioři; estrogeny; Hypogonadism; Obesity; Luteinizing Hormone; Androgens; hypogonadismus; androgeny; Česká republika; Middle Aged; mužské pohlaví; Adult; mladý dospělý; Czech Republic; luteinizační hormon; Young Adult; Humans; Follicle Stimulating Hormone; Estrogens; Estradiol; folikuly stimulující hormon; lidé středního věku; obezita; dospělí; Aged; estradiol; lidé; Male